Electron energy can oscillate near a crystal dislocation. (25th January 2017) - Li, Mingda; Cui, Wenping; Dresselhaus, Mildred S; Chen, Gang
Abstract: Crystal dislocations govern the plastic mechanical properties of materials but also affect the electrical and optical properties. However, a fundamental and quantitative quantum field theory of a dislocation has remained undiscovered for decades. Here we present an exactly-solvable one-dimensional quantum field theory of a dislocation, for both edge and screw dislocations in an isotropic medium, by introducing a new quasiparticle which we have called the 'dislon'. The electron-dislocation relaxation time can then be studied directly from the electron self-energy calculation, which is reducible to classical results. In addition, we predict that the electron energy will experience an oscillation pattern near a dislocation. Compared with the electron density's Friedel oscillation, such an oscillation is intrinsically different since it exists even with only single electron is present. With our approach, the effect of dislocations on materials' non-mechanical properties can be studied at a full quantum field theoretical level.